Implementasi Scientific Proses Pada Pembelajaran Fiqih Di MI Muhammadiyah Pone-Limboto - Zainul Romiz Koesry; Nasir, Merni; Akhmad, Enni (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2020)
Abstract The purpose of this research is to know the scientific implementation of the process on the Fiqh study, constraints and solutions on the MI Muhammadiyah Pone-Limboto West The approach used in this research is a descriptant approach with the type of research Qualitative. The results showed that: (1) The Scientific implementation of the process on Fiqh learning at the MI Muhammadiyah Pone-Limboto West, has been running quite well, where the teacher in learning using scientific approaches Observing activities, solicitation, trying, collecting information, associating, and communicating. (2) Constraints in the Scientific implementation of the process on Fiqh learning in MI Muhammadiyah Pone-Limboto west, namely the lack of understanding the teacher in the balance of learning with scientific approaches, Lack of interest in asking students, and the lack of infrastructure that supports learning in the form of learning resources is also one obstacle in implementing curriculum-based Learning 2013 using scientific prosecution. The solution that can be done by the school is to involve the teachers in seminars, trainings and training on the curriculum of 2013, and try to hold a learning resource in the form of books that are still lacking, by copying the book. Keywords: implementation, scientific approaches, fiqh learning, Muhammadiyah Pone MI.